Business on Nickel Downstreaming with China and European Union Lawsuits - Marwanto; I Nyoman Prabu Buana Rumiartha; Meliana Putri; I Wayan Parsa; I Gede Yusa (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
This study aims to discuss the law and investment business between China-Indonesian companies and the European Union lawsuit. China companies that build nickel refining and processing plants or smelters in Indonesia with large investment values, the Indonesian government obtains significant profits from exports through domestic processed nickel exports. The research method used in this study is the normative legal research method. The results of the study indicate that the benefits between Indonesia and China include China investment in Indonesia, job creation in Indonesia, and increased export results, which have an impact on concerns in the European Union, especially since Indonesia recently banned the export of nickel ore. On the contrary, Indonesia has encouraged domestic nickel ore processing to add value to nickel products. Indonesia as one of the largest nickel producers in the world has regulations regarding nickel exports. This is stated in the Regulation of the Minister of Energy and Mineral Resources Number 11 of 2019 concerning the Second Amendment to the Regulation of the Minister of Energy and Mineral Resources Number 25 of 2018 concerning Mineral and Coal Mining Business Activities. In the regulation, Indonesia imposed a ban on nickel ore exports. Regarding this ban, the European Union reacted by filing a lawsuit with the World Trade Organization (WTO). Based on the State sovereignty & Theory of Welfare State, the state must actively strive for welfare, and act fairly that can be felt by all people evenly and in balance. Therefore, the implementation of a ban or restriction on nickel ore exports is a way for the Indonesian government to improve people’s welfare. The narrative of national sovereignty and welfare state can be used as an argument in front of the WTO international forum but accompanied by a strong legal basis argument by using Article XIX of GATT 1994 regarding the exception in economic circumstances, a safeguard measure against domestic industry when there is a surge in imports that causes or threatens to cause serious losses.